Freedom's debtors : British antislavery in Sierra Leone in the age of revolution - Scanlan, Padraic X. (Lewis Walpole series in eighteenth-century culture and history., 2017)
A history of the abolition of the British slave trade in Sierra Leone and how the British used its success to justify colonialism in Africa.